2020
DOI: 10.1111/aphw.12236
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Perceived Physical Activity Transitions during the COVID‐19 Pandemic among Canadian Adults

Abstract: Background The purpose of this study was to explore socio‐ecological predictors of moderate to vigorous physical activity (MVPA) as a result of the COVD‐19 pandemic restrictions. Method A representative sample of 1,055 English‐speaking Canadians (18+ years) completed measures of MVPA during the COVID‐19 restrictions and reflecting on MVPA prior to these restrictions, as well as demographics, COVID‐19‐related cognitions and behavior (i.e. perceived threat, social distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
143
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(163 citation statements)
references
References 92 publications
18
143
2
Order By: Relevance
“…The lower-educated respondents and those living on the countryside significantly decreased their mean minutes of PA per week more than other subgroups. These findings are similar to other studies on PA behavior during the COVID-19 pandemic (López-Bueno et al, 2020 ; Rhodes et al, 2020 ). Unfortunately, low-educated individuals and residents living in rural areas are those who already are least likely to meet PA recommendations both inside (Pilgaard and Rask, 2016 ) and outside of Denmark (Parks et al, 2003 ) and, therefore, should be given special priority in public health promotion during and after the COVID-19 shutdown.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lower-educated respondents and those living on the countryside significantly decreased their mean minutes of PA per week more than other subgroups. These findings are similar to other studies on PA behavior during the COVID-19 pandemic (López-Bueno et al, 2020 ; Rhodes et al, 2020 ). Unfortunately, low-educated individuals and residents living in rural areas are those who already are least likely to meet PA recommendations both inside (Pilgaard and Rask, 2016 ) and outside of Denmark (Parks et al, 2003 ) and, therefore, should be given special priority in public health promotion during and after the COVID-19 shutdown.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, low-educated individuals and residents living in rural areas are those who already are least likely to meet PA recommendations both inside (Pilgaard and Rask, 2016 ) and outside of Denmark (Parks et al, 2003 ) and, therefore, should be given special priority in public health promotion during and after the COVID-19 shutdown. The study also found a significant disparity in PA behavior among the different age groups, which is supported by previous studies on PA behavior during the COVID-19 pandemic (Cheval et al, 2020 ; López-Bueno et al, 2020 ; Maugeri et al, 2020 ; Ong et al, 2020 ; Rhodes et al, 2020 ; Rogers et al, 2020 ; Yamada et al, 2020 ) and discussed in the following.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Further, results revealed that before-lockdown PA habits were not significantly related with mid-lockdown PA behaviours. Although a previous study found a significant association between previous habits and PA behaviours during lockdown (Rhodes et al, 2020), the strength of the association (r = .24) was weaker than the commonly reported relationship between habits and behaviours (r = .43) (Gardner et al, 2011). These results can be explained by the fact that, during lockdown, some contextual cues were no longer encountered during lockdown (e.g., going to the gym club on Wednesdays after work with colleagues), which, in turn, made habits dormant and impeded their influence on behaviours (Gardner, 2012).…”
Section: Comparisons With Other Studiesmentioning
confidence: 70%
“…Among other determinants, PA habits appear as one potential factor explaining these changes (Kaushal et al, 2020;Rhodes et al, 2020).…”
Section: Lockdownmentioning
confidence: 99%